Studi kasus prospek usaha kerupuk ikan di Kampung Semanting Kabupaten Berau: Case study of fish cracker business prospect at Semanting Village, Kabupaten Berau - Aulia Asmaul Husna; Helminuddin; Fitriyana (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2022)
Semanting village is well known for its natural resources. Fishing and its related produce has been identified as the main home industry in this village. One of the most popular fish produce is fish cracker managed by Hj. Asfiah. The main ingredient of this product is milk fish (chanos-chanos) and otek fish (Osteogeneiosus militaris). In order to identify the internal and external strategy of this business, the SWOT analysis was applied to evaluate strength, weakness, opportunity and threat that might affect the business sustainability. The analysis indicated that the strength and opportunity (S-O) is essential and need to be managed. Based on the estimation values, this business is feasible and scale improvement is necessary.